Capacitive MEMS accelerometers testing mechanism for auto-calibration and long-term diagnostics - L. A. Rocha (2007)
A test technique for capacitive MEMSaccelerometers and electrostatic micro-actuators based onthe measurement of pull-in voltages is described. Acombination of pull-in voltages and resonance frequencymeasurements can be used for the estimation of processinducedvariations in device dimensions from layout anddeviations in material properties from nominal value,which enables auto-calibration. Preliminary measurementson fabricated devices confirm the validity of the proposedtechnique. Moreover, long-term pull-in measurements haveindicated the suitability of the approach as in-systemdiagnostic tool.